Comparative Analysis of Personal Hygiene Practices of Rural and Urban Female Secondary School Students in Obio/Akpor Local Government Area, Rivers State - Kpe-Nobana, L. Christiana; Amaigbani, ThankGod (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2024)
This study compared the personal hygiene practices among female secondary school students in Obio/Akpor Local Government Area of Rivers State. Five research questions and five hypotheses guided the study. Comparative research design was adopted for the study, with a population consisting of 7,000 female students. A sample size of 190 was selected using the simple random sampling technique. Data collection was done using a structured questionnaire titled ‘Personal Hygiene Questionnaire (PHQ)’, with a reliability coefficient of 0.70. The reliability was tested using Cronbach Alpha. Data analysis was done using mean and z-test at 0.05 level of significance. The result revealed that personal hygiene practices such as oral hygiene ( = 3.36±0.82 vs 3.27±0.88); and hand hygiene ( = 3.25±0.89 vs 3.11±0.88) were practised more in rural areas than in the urban areas while others, such as cloth hygiene ( = 3.62±0.53 vs 3.61 ±0.56); body hygiene ( = 3.38±0.86 vs 3.34 ±0.94); and menstrual hygiene ( = 3.66±0.56 vs 3.32 ±1.06) were practiced more in urban areas than rural areas. There was no statistically significant difference in the personal hygiene (oral hygiene, hand hygiene, cloth hygiene, body hygiene, menstrual hygiene) practices among female student in rural and urban areas (p>0.05). In conclusion, personal hygiene was practised more in urban areas than in the rural areas, specifically cloth, body and menstrual hygiene. However, the government should organize health education programmes on the body hygiene of the girl child, in the different secondary schools in the State to enhance their personal hygiene practices.